(untitled) (Baghdad Science Journal, 2025)
Pregnancy- including hypertension(PIH), also known as preeclampsia, is one of the major causes of maternal and fetal death. This study was carried out on 30 pregnant women with preeclampsia and 30 healthy pregnant women as control ranging in age mean ±SD (28.84±3.55) years , BMI (76.80±9.78) Kg/m2 and gestation age(30.82±0.75)week. The aim of this research was studied the plasma Metanephrine level and other biochemical parameters such as Hemoglobin(Hb), serum Protein, S. Albumin, Globulin, Albumin/Globulin ratio (Alb/Glu. ratio), S.Glutamate Pyruvate aminotransferase (GPT), S.Glutamate Oxaloacetate aminotransferase(GOT). The obtained results have been compared with 30 healthy pregnant women as control group. The result showed that there was significant increase in mean value of Hb in group A(pregnant women with preeclampsia) when compared to group B(healthy pregnant women). The present study showed no significant changes was observed in the level of S. Protein, globulin, Alb./Glu. ratio, GPT and GOT as compared to control group. While Albumin showed a significant decrease in group A(pregnant women with preeclampsia) when compared with group B(healthy pregnant women) and significant increase in the levels of metanephrine, metanephrine/protein ratio, metanephrine/Alb ratio in group A (pregnant women with preeclampsia) to group B(healthy pregnant women).The present study conclude that the increase in the levels of metanephrine, metanephrine/protein ratio, metanephrine/Alb ratio in pregnant women with preeclampsia may be used as a marker to evaluate the development of disease. The current study recommend to take more case and measurement metanephrine in plasma and urine.